Reason of pitting corrosion of martensitic steel in sea water - Baikenov, M.I.; Seldyugaev, O.B.; Guchenko, S.A.; Afanasyev, D.A. (Karagandy University of the name of acad. E.A. Buketov, 2024)
The assumption that corrosion of products from X17 martensitic stainless steel in seawater occurs due to incomplete oxidation of chromium atoms in cells on the surface of the products is made in the presented work. Incomplete oxidation of chromium atoms occurs in the cells of X17 steel. This is due to the fact that oxygen molecules at temperatures up to 350 °C not having enough energy for chemical interaction with trivalent chromium atoms entering the cubic body-centered cells of martensitic stainless steel. There is a significant decrease in the corrosion rate after placing X17 stainless steel products in 5% iodine solution in ethanol after pre- treatment of the product surface with active forms of oxygen. The treatment was carried out during 12 hours with chemically active forms of oxygen (ozone and singlet oxygen) at a temperature of 350 °С. Most of the chromium atoms on the surface of X17 steel samples were completely oxidized as a result of 12 hours exposure to highly active forms of oxygen. The density of the oxide passivation layer on the surface of the products increased significantly as a result of the formation of new bonds CHROMIUM - OXYGEN - CHROMIUM. This resulted in increased corrosion resistance. The rate of interaction with an alcohol solution containing halogen ions was reduced by 71% for the samples with the oxide passivation layer compared to samples of untreated X17 steel.
Keywords: carbon steel; seawater; localized corrosion; oxidation; halogens; body-centered cubic structure